Knowledge and attitude regarding organ donation among undergraduate medical students in a tertiary healthcare centre - Kumar, Gopal; Verma, Ramesh; Agrawal, Ginni; Sachdeva, Aman (International Journal Of Community Medicine And Public Health, 2020)
Background: In India the rate of organ donation is less than 1 per million population. The need for organ transplantation is more than 5 lakhs per year. There is a wide discrepancy between demand and donation. Health care professionals can play a vital role in creating awareness in the society and encouraging the people to donate organs and thus help in filling the gap between the demand and donation. Aim of the study was to assess the knowledge and attitude regarding organ donation among medical students. Methods: A 24 item semi structured and self-administered questionnaire was used to assess the knowledge and attitude regarding organ donation from 300 undergraduate medical students in PGIMS, Rohtak. Data was collected, compiled and analyzed using SPSS. Results: The awareness regarding different organ donation was found to be kidney (79%), liver (70.7%), heart (61%), intestine (3.7%), and lung (10.3%). 28% participants were knowing about NOTTO (National organ and tissue transplant organization). 85% participants were willing to donate their organs. Conclusions: There is good knowledge and positive attitude towards organ donation among undergraduate medical students. But their attitude is not being transformed into organ donation. Separate chapters on organ donation and its need in our country should be included in the school curriculum, interactive sessions should be held in medical colleges and opportunities should be given to them during their college life to voluntarily donate their organs, only then we can cultivate their positive attitude and knowledge.